2019
DOI: 10.1155/2019/7208494
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of an Augmented Reality Application on Learning Motivation of Students

Abstract: The research on augmented reality applications in education is still in an early stage, and there is a lack of research on the effects and implications of augmented reality in the field of education. The purpose of this research was to measure and understand the impact of an augmented reality mobile application on the learning motivation of undergraduate health science students at the University of Cape Town. We extend previous research that looked specifically at the impact of augmented reality technology on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
231
0
29

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 366 publications
(273 citation statements)
references
References 21 publications
13
231
0
29
Order By: Relevance
“…AR technology can offer opportunities to create a user-friendly and immersion learning environment that can be a useful environment for learning (Huang & Liaw, 2014). The mobile augmented reality application increases student learning motivation (Khan et al, 2019). Attention, satisfaction, and motivational confidence factors increase, and these results are found to be significant (Huang & Liaw, 2014;Khan et al, 2019;Mahadzir & Phung, 2013;Sonntag et al, 2019).…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…AR technology can offer opportunities to create a user-friendly and immersion learning environment that can be a useful environment for learning (Huang & Liaw, 2014). The mobile augmented reality application increases student learning motivation (Khan et al, 2019). Attention, satisfaction, and motivational confidence factors increase, and these results are found to be significant (Huang & Liaw, 2014;Khan et al, 2019;Mahadzir & Phung, 2013;Sonntag et al, 2019).…”
Section: Resultsmentioning
confidence: 97%
“…The gain score of experimental group is higher than the control group, it is shown that AR media is very effective in increasing learning motivation and working optimally for student learning motivation. According to Khan, Johnston, and Ophoff (2019) AR media can involve students and motivate them to explore in the context of immersion between teaching materials from the real world with virtual objects created by AR technology. The results of previous studies also showed that immersion and interactivity factors were two predictors for student motivation (Huang & Liaw, 2014;Iftene & Trandabăț, 2018;Khan et al, 2019;Lee, 2012;Sonntag et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Khan, Johnston, dan Ophoff (2019) menggunakan model Attention, Relevance, Confidence, dan Satisfaction (ARCS) untuk mengukur dampak penggunaannya. Dari total 78 responden yang mengisi kuesioner didapat bahwa faktor attention, satisfaction, confidence meningkat signifikan dengan adanya pemakaian aplikasi AR (Khan, Johnston, & Ophoff, 2019). Medina, García, dan Olguín (2018) melakukan perencanaan dan alokasi Digital Learning Object (DLO) berbasis AR menggunakan VARK model untuk siswa higher education.…”
Section: Pendahuluanunclassified
“…The application in teaching and learning for teaching and learning of Islamic Study [6]. Recently, Khan et al [7] studied the impact of an AR application on learning motivation of students. They reported many authors own mobile device and therefore have access to AR.…”
Section: Introductionmentioning
confidence: 99%